THE EFFECTIVENESS OF THE THINK PAIR SHARE OF COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES - Zuul Fadhil Adhim; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
This research aims to determine the effectiveness of student mathematics learning outcomes in learning using the Think Pair Share (TPS) method. This research population is all VII grade students of State Islamic Junior High School (MTs Negeri) 1 Yogyakarta in the odd semester of 2019/2020 academic year, consisting of 3 study groups totaling 80 students. Samples were taken from two classes using random sampling techniques. They obtained grade VII C as an experimental class and class VII B as a control class. The instrument used in this study was a test. While the data analysis technique for the prerequisite test uses the normality test with the Chi-Squared formula, the homogeneity test with the Barlet test formula, the hypothesis test uses the t-test. The study results at a significant level of 5% degrees of freedom = 52 indicate that testing of the hypothesis test I results in learning using the TPS learning method effectively against student learning outcomes. Â which is 4.223199279>1.674, then H0 is rejected.